Local Fashion Shopping Preferences in Generation Z From Product and Ethnocentric Perspective: Preferensi Belanja Fashion Lokal pada Generasi Z dari Perspektif Produk dan Etnosentris - Sesilya Kempa; Jessica Budianto (Universitas Muhammadiyah Sidoarjo, 2025)
The development of fashion in the digital era is increasingly rapid, driven by the online shopping trend which offers convenience and flexibility for consumers, especially Generation Z. This study aims to examine the factors that influence the willingness of Generation Z in Indonesia to buy local fashion products, with a focus on consumer ethnocentrism, product evaluation, and perceived value. This research uses quantitative methods and uses a sampling technique, namely non-probability sampling. The sample in this study involved 207 respondents from Generation Z. The data analysis technique used was Partial Least Square analysis. The results of this research show a significant influence between product evaluation and consumer ethnocentrism on willingness to buy local fashion brands through perceived value. The perceived value variable is also a good mediator for the relationship between Product evaluation and consumer ethnocentrism in willingness to buy local fashion products. However, there is an insignificant direct relationship between product evaluation and consumer ethnocentrism with willingness to buy. The research results provide insight into strategies that can be adopted by local brands in facing competition and support increasing the competitiveness of local fashion products in the market.